DISHARMONISASI PENGATURAN PENGELOLAAN PENGADAAN TANAH BAGI KEPENTINGAN PROYEK STRATEGIS NASIONAL - Gantika, Naldi; Novianti, Novianti (Ensiklopedia Education Review, 2023)
Abstract: Civil law in Indonesia is basically based on Napoleonic Law and then based on Staatsblaad Number 23 of 1847 concerning Burgerlijk Wetboek for Indonesia (abbreviated as BW) or referred to as the Civil Code. BW is actually a legal regulation made by the Dutch East Indies government aimed at non-native citizen groups, namely Europeans and Chinese. However, based on article 2 of the transitional regulations of the 1945 Constitution, it is written "All State Bodies and Regulations that existed until the founding of the Republic of Indonesia on August 17 1945, as long as new ones have not been implemented according to the Constitution," are still in effect. And several provisions contained in the BW have currently been regulated separately or separately by various statutory regulations, for example relating to land, mortgage rights and fiduciaries.Keywords: Disharmonization, Management Arrangements, Land Acquisition. National Strategic.